The SPIRITUALITY AND STRESS: BIBLIOMETRIC ANALYSIS OF THE CURRENT STATE OF THE ARTICLES AND PERSPECTIVE: SPIRITUALITAS DAN STRES: ANALISIS BIBLIOMERIK TERHADAP STATUS ARTIKEL DAN PERSPEKTIF TERKINI - Rahmadany, Muhammad Fa'iz; Munawaroh, Siti; Wiyono, Nanang; Hastami, Yunia (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2022)
Introduction: to learn more about and comprehend the most recent studies on spirituality and stress. This study assesses pertinent themes connected to spirituality and stress through bibliometric analysis using the keyword